Evaluasi Pembelajaran Projek Di TK Negeri Pembina Kabupaten Seluma - Herlina, Yuni; Haryono, Mimpira (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
Project-based learning is one approach used in the Independent Curriculum to increase the active involvement of early childhood children in the learning process. This study aims to evaluate the implementation of project-based learning at Pembina State Kindergarten in Seluma Regency. The method used was descriptive qualitative through observation, interviews, and documentation. The evaluation results indicate that although project-based learning has been implemented, several obstacles remain, such as uneven teacher understanding, limited facilities, and varying parental involvement. Recommendations are provided for improving teacher training, providing learning resources, and strengthening partnerships with parents.